A study on daylight performance through various complex shading devices in Kuala Lumpur, Malaysia - Tahir, Amal; Denan, Zuraini; Hashim, Muhammad Hafizi (2010)
A lot of Shading Devices designs have been developed over the years to filter daylight into buildings. Complex shading devices which are characterised such as geometrical pattern, intense egg-grate configurations and irregular organic shapes are popular in Malaysia and rarely been investigated. These types of shading devices are significant in the language of Malaysian architecture as they are frequently characterized as having the identity of Malaysian Architecture. This paper aims to investigate the daylight performance through the complex shading devices based on three buildings located in Kuala Lumpur, Malaysia. The data is based on field measurement, observation and the subjective response of occupants in the buildings. The results will show the range of light illumination besides the satisfaction of occupants while doing their tasks by assistance of daylight in office building.The findings cover the illuminance level and subjective responses of the occupants.